Rapid Isolation of Circulating Tumor Cells from Glioblastoma Patients Using a Lateral Filter Array Microfluidic Device - Victória D’Amario Gavioli; Marcos Vilas Boas Filho; Gustavo R. Castro; Pedro Tadao Hamamoto Filho; Adriana Camargo Ferrasi; Valber A. Pedrosa (Chemosensors)
Glioblastoma is the most common form of brain cancer in adults, representing 35–40% of all malignant brain tumors. This highly aggressive malignancy originates in the central nervous system, and despite notable advancements in treatment strategies, it continues to be an incurable disease. The isolation of circulating tumor cells (CTC) at an early stage is challenging due to the low probability of their presence in peripheral blood. Detection and enumeration as early as possible can reportedly lead to more effective treatment. This study proposes a novel label-free, rapid, and continuous CTC separation device based on a lateral filter array microfluidic device for the highly efficient immunoaffinity isolation of CTCs. Our methodology successfully captured and isolated circulating tumor cells (CTCs) from the whole blood of glioblastoma (GBM) patients prior to surgery, achieving over 90% capture efficiency in under 40 min of analysis. These findings highlight the potential of this technology to enhance our understanding of the clinical significance of CTCs in the management of GBM in future research.